Perbuatan Tercela Sebagai Salah Satu Alasan Pemakzulan Presiden Dan/Atau Wakil Presiden Dalam Kajian Hukum Pidana Di Indonesia - Muhammad Irham; Nani Mulyati (Faculty of Law, Universitas Pattimura, 2021)
The purpose of this study is to find out what is meant by the President and/or Vice President committing a disgraceful act in the concept of criminal law, so that they can be impeached. By using normative legal research and approaches to legal concepts, laws and their history. The results of the research are as follows: First, all actions that are contrary to the Criminal Code are disgraceful acts for the President/Vice President; Second, the religious values, social culture of the Indonesian nation, as well as moral principles in the Criminal Code have been compiled in Pancasila and the 1945 Constitution, therefore any deviation from the behavior of the President/Vice President against the 1945 Constitution is a despicable act; Third, all disgraceful acts of the President/Vice President that violate criminal law offenses are subject to criminal sanctions in accordance with the Criminal Code, so that disgraceful acts that have been formally regulated in the Criminal Code are not the meaning of disgraceful acts as referred to in Article 7A of the 1945 Constitution, because the limitations of criminal acts have been determined can impeach the President/Vice President, namely: corruption, bribery, and other serious crimes; Fourth, the disgraceful act of the President/Vice President in Article 7A of the 1945 Constitution is an act of violating the 1945 Constitution as a reference to the rules of criminal law.